The Application of the Quantum Teaching Model with a Deep Learning Approach to Improve Students’ Problem-Solving Skills in the Topic of Static Fluids - Dhea Kamelia Fauziah; Muslim; Hera Novia; Devi Eliviani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze students’ problem-solving skills through the application of the Quantum Teaching model with a deep learning approach to static fluid. The research method used is a quantitative method with a between-group design, specifically a quasi-experimental research design. The type of quasi-experimental research design used in this study is a nonequivalent control group design, in which there are two classes used, namely a control class and an experimental class. The research instrument used is a problem-solving ability instrument developed based on Polya’s indicators, consisting of three items. The data analysis employed N-Gain scores and a t-test hypothesis test, which met the prerequisites of normality and homogeneity. The results indicate that the N-Gain scores in the experimental class were higher than those in the control class, with respective values of 0.71 and 0.42. These results were supported by the t-test hypothesis test, which showed an Asyimp sig (2-tailed) value—under the assumption of unequal variances—of <0.05. This indicates a significant difference in the improvement of problem-solving skills between students in the experimental and control classes. Thus, the Quantum Teaching model with a deep learning approach can serve as an alternative for enhancing problem-solving skills students, particularly in the area of static fluids.